Edukasi Cuci Tangan Untuk Meningkatkan PHBS Pada Siswa SDN 9 Kelapa Kabupaten Bangka Barat - Asti, Arnika Dwi; Yuliana, Elsa Dwi; Nugroho, Irmawan Andri (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Clean and healthy living behavior (PHBS) in the school environment is a set of behaviors that are practiced by students, teachers, and the school environment community as a learning outcome. The problems that arise in Kelapa 9 Public Elementary School show that students do not practice PHBS habits, such as rarely washing hands with soap and running water, rarely using healthy latrines, rarely disposing of trash in its place resulting in several cases of diseases such as diarrhea, DHF, intestinal worms, typhoid, and ulcer. Objective: The purpose of this service was to provide knowledge and understanding of PHBS to school children. In this case the students of SDN 9 Kelapa, West Bangka can practice it in their daily lives. Method: This public service was conducted by counseling with material on clean and healthy living behaviour and  watching the 6 correct steps to wash your hands Result: After conducting counseling and practicing hand washing, the results were: 22 students (100%) were able to rub their hands by bringing their palms together in the good category; 22 students (100%) could rub the palm of their hand against the back of their hand in the good category; 20 students (96%) were able to practice both palms together and fingers intertwined in the good category and 2 students (4%) did it in the sufficient category; 17 students (90%) could place the back of their fingers on the palm with the fingers locked in the good category, 4 students (8%) did it in the sufficient category and 1 student (2%) was in the poor category; 16 students (88%) performed rubbing and rotating the right thumb in the good category, 4 students (8%) in the sufficient category and 2 students (4%) in the poor category; 22 students (100%) could place the five fingers of the left hand on the palm of the right hand, rotate it forward and backward in the good categoryConclusion: Hand washing education and practice can increase knowledge and understanding about clean and healthy living (PHBS) among SDN 9 Kelapa school students.